1, 4‐Dithiane‐2, 5‐diol: An Attractive Platform for the Synthesis of Sulfur‐Containing Functionalized Heterocycles. Issue 25 (1st June 2018) - Zamberlan, Francesco; Fantinati, Anna; Trapella, Claudio
Abstract : This microreview highlights the utility of 1, 4‐dithiane‐2, 5‐diol (1 ) as a source for the in situ generation of 2‐mercaptoacetaldehyde (2 ), a versatile two‐carbon synthon featuring both electrophilic and nucleophilic reaction centres and widely utilized as an attractive platform for the preparation of sulfur‐containing molecules. We discuss the chemistry involved, mainly focusing on its applications to the construction of sulfur‐containing heterocyclic compounds including the thiophene and 1, 3‐thiazole families and other different sulfur–nitrogen and sulfur–oxygen heterocycles that continue to be a pillar of organic synthesis as a result of their broad application in organic and medicinal chemistry. Abstract : This microreview highlights 1, 4‐dithiane‐2, 5‐diol as a cheap, commercially available source for in situ generation of mercaptoacetaldehyde. A versatile synthon featuring both electrophilic and nucleophilic reaction centres, it is useful for the preparation of sulfur‐containing heterocycles, such as thiophenes and 1, 3‐thiazoles, which are important in natural products and in medicinal chemistry.